Fair scheduling algorithm in LTE-advanced networks - Al-Shibly, Mohammed Abuljawad M; Habaebi, Mohamed Hadi; Islam, Md Rafiqul; Chebil, Jalel; Zyoud, Alhareth; Alfaqawi, Mohammed I M (Asian Research Publishing Network (ARPN), 2015)
The Long Term Evolution Advanced (LTE-Advanced) transmission bandwidth can be expanded by Carrier Aggregation (CA), where CA technology expands effective bandwidth supported to User Equipment (UE) by utilizing of radio resources across multiple carriers. Recently, many studies have been conducted on the radio resource allocation with CA. However, most of these studies are based on Proportional Fair (PF) packet scheduling algorithms. Indeed, these algorithms are not adequate to meet the requirements for supporting mixture real-time applications; they ignored channel condition; and finally, they are unable to support real-time application with delay constraint. Therefore, this paper proposes novel Packet Scheduling (PS) condition algorithm that attractively enhances the average system throughput by designing a weighting factor to modified largest weighted delay first PS algorithm. The novel algorithm is implemented in a PS module for LTE-Advanced via system level simulations. The results demonstrate that the effectiveness of enhanced Modified Largest Weighted Delay First (M-LWDF) algorithm in improving throughput.